Ipilimumab and nivolumab in the treatment of recurrent malignant pleural mesothelioma (INITIATE): results of a prospective, single-arm, phase 2 trial. Issue 3 (March 2019) - Disselhorst, Maria J; Quispel-Janssen, Josine; Lalezari, Ferry; Monkhorst, Kim; de Vries, Jeltje F; van der Noort, Vincent; Harms, Emmy; Burgers, Sjaak; Baas, Paul
Summary: Background: Single-drug checkpoint inhibition has shown efficacy in patients with recurrent malignant pleural mesothelioma. Here, we assessed the safety and efficacy of the combination of nivolumab, an anti-programmed cell death 1 antibody, plus ipilimumab, an anti-cytotoxic T-lymphocyte protein 4 antibody, in patients with previously treated and relapsed malignant pleural mesothelioma. Methods: INITIATE was a prospective single-centre, single arm, phase 2 trial. Patients with malignant pleural mesothelioma who progressed after at least one line of platinum-containing chemotherapy were enrolled. Key eligibility criteria were measurable disease according to the modified Response Evaluation Criteria in Solid Tumours for mesotheliomas, Eastern Cooperative Oncology Group performance status 0 or 1, and adequate organ function. Patients received intravenous nivolumab (240 mg every 2 weeks) plus intravenous ipilimumab (1 mg/kg every 6 weeks up to four times). Treatment was continued for up to 2 years or until confirmed progression or unacceptable toxicity. The primary endpoint was disease control at 12 weeks. All patients who received at least one dose of therapy were included in safety analysis and all patients who received one dose of therapy and at least one radiological assessment were included in the primary analysis. This trial is registered atClinicalTrials.gov, numberNCT03048474 . Findings: Between Oct 5, 2016, and Aug 3, 2017, 38 patients were enrolled in the study, of which two patients were excluded because they were not eligible for a biopsy. Of 36 eligible patients, one deteriorated before the start of the study so was not included in any analyses and one withdrew consent after one treatment cycle before radiological assessment so was included in the safety population only. 34 patients were evaluable for response assessment at 12 weeks. Of these, ten (29%) patients had a partial response and 13 (38%) patients had stable disease; thus, disease control was achieved by 23 (68%, 95% CI 50–83) of 34 patients. Treatment-related adverse events were reported in 33 (94%) patients. The most common adverse events were infusion-related reactions, skin disorders, and fatigue. Grade 3 treatment-related adverse events were reported in 12 (34%) of 35 patients. Interpretation: In this single-centre phase 2 trial, the combination of nivolumab plus ipilimumab showed marked efficacy in patients with recurrent malignant pleural mesothelioma. The safety profile was consistent with known data on the combination regimen. Our results warrant further investigation of this combination in a phase 3 trial. Funding: Bristol-Myers Squibb.